Peran Media Sosial X Sebagai Sarana Orang Tua dalam Mendukung Perkembangan Remaja Berdasarkan Perspektif Analisis Jurnalisme - Martial, Abdullah Alfath; Saragih, Muhammad Yoserizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This research examines the role of social media X as a tool for parents in supporting adolescent development through a journalistic perspective, using The Social Theory of Reality Construction and Media Exposure Theory. Social Reality Construction Theory and Media Exposure Theory explain that social interaction and continuous exposure to content on X allow parents and teenagers to construct, maintain, and shape their social reality perceptions. This research uses a qualitative approach with a descriptive research type to understand how parents use X in supporting adolescent development. The research stages include subject identification, data collection through in-depth interviews and participatory observation, and data analysis using content analysis techniques. Data collection techniques included interviews, participatory observation, and documentation. To ensure data validity, data triangulation was used. The results showed that teenagers' use of X is influenced by peer factors and interest in certain information. Parental supervision of X use still needs to be improved. Parents who are more involved in their children's social media activities tend to have closer relationships and can provide more effective guidance. Effective strategies include intensive digital education, continuous engagement, activity monitoring, communication guidance, and appropriate educational approaches. This research emphasizes the importance of parents' active role in assisting their children to use social media positively and responsibly.